Research as an axis for business development - Barragán Morales, Camilo; Barragán Morales, Camilo (Corporación Universitaria Americana, 2020)
2020 has been a year full of adverse and above all challenging conditions for all spheres of society, although true, the COVID-19 pandemic brought with it new scenarios and dynamics, advances in research have not been left behind; Therefore, it is imperative the articulation between state agencies, higher education institutions, representing the edge of the academy, and organizations.